A study on interfacial activities between Nb and liquid Al in static and dynamic condition. (2020) - Biswas, Prasenjit; Patel, Deepak; Kumar, Anil; Bagani, Aaryan; Soni, Pranjal; Kotadia, R. Hiren; Das, Sanjeev
Abstract: In the present study, an effort has been made to investigate the interfacial activities between the solid Niobium and liquid Aluminium. Aluminium was melted at 750 °C temperature and subsequently, solid niobium was immersed into the liquid aluminium and held for different time intervals. The study was conducted in static as well as dynamic conditions. Temperature and time were similar for both static and dynamic conditions. After solidification, the Nb-Al interface was studied under optical microscopy, scanning electron microscopy, EDS and X-Ray diffraction analyzer. The analysis revealed that there was no change in the dimension of Nb sample and no intermetallic compound formed on the surface or subsurface of solid Niobium under present experimental condition.